Development of Reading Competence of Non-Philological University Students Through Vocational Texts (On the Example of the English Language) - Soliyev, Umidjon (Indonesian Journal Publisher, 2024)
This article is devoted to the methodical problem of teaching reading in English classes, and the description of the methodical problem of teaching reading in English classes is widely covered. It has been suggested that teaching the language based on English texts in English classes is a more effective method, but the development of reading competence in vocational English teaching has not been thoroughly studied. The article also presents the scientific research and expected results on the use of English texts in vocationally oriented English teaching.